Monkey party (Australia : Heinle, Cengage Learning, 2009)
Describes the importance of monkeys in Thailand and includes questions, definitions, and a vocabulary list
'National geographic' - cover
Book is accompanied by one DVD, entitled'Monkey party' bearing the same call number and available at Bahagian Koleksi Media
Keywords: English language -- Textbooks for foreign speakers; Monkeys